Statistical Convergence of order ? for Double Sequences of Fuzzy Numbers Defined by a Modulus Function - Altinok, Hifsi; Altin, Yavuz; Isik, Mahmut (Amer Inst Physics, 2018)
In the present paper, we extend the notions of statistically convergence of order beta and strong Cesaro summability of order beta for sequences of fuzzy numbers and introduce the notions of f-statistically convergence of order beta and strong Cesaro summability of order beta for beta is an element of (0, 1] with respect to an unbounded modulus function f for double sequences of fuzzy numbers and give some inclusion theorems.
6th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 15-17, 2017 -- Budapest, HUNGARY
Keywords: Generalized Difference-Sequences; Alpha; Spaces